Engaging performance : theatre as call and response - Cohen-Cruz, Jan (London : Routledge, 2010)
Contents: Playwrighting : putting plays to use -- Specta(c)ting : theatre of the oppressed, orthodoxy and adaptation -- Self-representing : testimonial performance -- Cultural organizing : multiple modes of communication -- Gathering assets : the art of local resources -- Particularizing place : revitalizing cities and neighborhoods -- Training : an engaged artist prepares.
boek